2019
DOI: 10.1098/rstb.2018.0185
|View full text |Cite
|
Sign up to set email alerts
|

Sparse evidence for selection on phenotypic plasticity in response to temperature

Abstract: One contribution of 13 to a theme issue 'The role of plasticity in phenotypic adaptation to rapid environmental change'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(137 citation statements)
references
References 110 publications
2
115
3
Order By: Relevance
“…If the trait in question is a component of fitness that may vary across the environment, this covariance can even be interpreted as a test of costs or benefits of plasticity in the fitness component. A useful extension, which allows an analysis of selection on plasticity, is to use a bivariate model combining a random regression of the focal trait with a basic model of measures of individual fitness: here, the covariance between trait slopes and individual fitness represents selection on plasticity (Arnold et al ., in press; for empirical examples see Hayward et al ., ; Boulton et al ., ). Furthermore, where plasticity in multiple traits has been measured, a multivariate mixed model can also be used to analyse plastic responses in several traits, and will return estimates of covariances between the different traits in both intercepts and slopes (e.g.…”
Section: Random Regression Mixed Model Frameworkmentioning
confidence: 99%
“…If the trait in question is a component of fitness that may vary across the environment, this covariance can even be interpreted as a test of costs or benefits of plasticity in the fitness component. A useful extension, which allows an analysis of selection on plasticity, is to use a bivariate model combining a random regression of the focal trait with a basic model of measures of individual fitness: here, the covariance between trait slopes and individual fitness represents selection on plasticity (Arnold et al ., in press; for empirical examples see Hayward et al ., ; Boulton et al ., ). Furthermore, where plasticity in multiple traits has been measured, a multivariate mixed model can also be used to analyse plastic responses in several traits, and will return estimates of covariances between the different traits in both intercepts and slopes (e.g.…”
Section: Random Regression Mixed Model Frameworkmentioning
confidence: 99%
“…Within-individual plasticity can be advantageous since it can allow individuals to respond immediately to ongoing environmental heterogeneity (Houston & McNamara, 1992), for example adapting condition-dependent decision-making to the current conditions. However plasticity is not always adaptive (Arnold, Nicotra, & Kruuk, 2019;Gotthard & Nylin, 1995): changes in phenotype may simply reflect physiological constraints or resource limitation, and flexibility may also come at a cost (DeWitt, Sih, & Wilson, 1998). Nevertheless, whether or not average plasticity is adaptive, variation in reaction norms would imply the potential for selection on plasticity.…”
mentioning
confidence: 99%
“…This study follows the one-step approach demonstrated by Arnold et al (2019), using a bivariate generalized linear mixed model to assess selection pressures on LDBD and CSLD reaction norms. We illustrate the approach here with the LDBD reaction norm.…”
Section: Assessing Selection Pressures On Reaction Normsmentioning
confidence: 99%
“…Nussey et al, 2005). The latter is essentially stats-on-stats, where statistical errors in Step 1 would be carried over to Step 2 (Arnold et al, 2019). In addition, to perform Step 2, one can either utilize estimates from a simple linear regression, or best linear unbiased predictors (BLUP) of random effects from mixed models in Step (Brommer et al, 2012).…”
Section: Bivariate Random Regression Models To Estimate Selectionmentioning
confidence: 99%
See 1 more Smart Citation